The translational aspect of complementary and alternative medicine for cancer with particular emphasis on Kampo - Amitani, Marie; Amitani, Haruka; Sloan, Robert A.; Suzuki, Hajime; Sameshima, Nanami; Asakawa, Akihiro; Nerome, Yasuhito; Owaki, Tetsuhiro; Inui, Akio; Hoshino, Etsuo (Frontiers in Pharmacology, 2015)
Complementary and alternative medicine (CAM) including Japanese Kampo is known to have anticancer potential. An increasing number of cancer survivors are using CAM for disease prevention, immune system enhancement, and symptom control. Although there have been abundant previous clinical reports regarding CAM, scientific investigations aimed at acquiring quantifiable results in clinical trials, as well as basic research regarding CAM, have only recently been undertaken. Recent studies suggest that CAM enhancement of immune function is related to cytokines. This review provides a translational aspect of CAM, particularly Hozai in Kampo from both scientific and clinical points of view for further development of CAM for cancer treatment.